Predictors of food security status among informal caregivers of older adults residing in slums in Ghana - Dina Adei; Williams Agyemang-Duah; Bright Osei Boateng; Anthony Acquah Mensah (BMC Public Health)
Abstract Background Informal caregivers of older adults play a crucial role, positively influencing the physical, mental, and social well-being of their care recipients, while concurrently contributing to substantial cost savings in the healthcare sector. The significance of food security for these caregivers becomes paramount as it not only impacts their health but also influences the energy needed to fulfil their caregiving responsibilities. Nevertheless, there is a scant literature on the factors that predict food security status among informal caregivers of older adults residing in slum communities in Ghana. This study seeks to address this gap by examining the factors that predict food security status among informal caregivers. Methods A sample of 458 informal caregivers of older adults residing in slum communities in the Greater Kumasi metropolis was used for the study. The Generalized Linear Regression Model was used to estimate factors that predict food security status among informal caregivers of older adults in slum communities. Beta values and standard errors were utilised, with a significance level of 0.05 or lower. Results The analysis showed that 88.4% of the participants were females, 37.3% were aged 40–49 years, 72.7% were of Akan ethnicity, 81.4% were married, 45.4% had basic education, 96.3% did not receive pay for caregiving and 72.1% were enrolled in a national health insurance scheme. The study revealed that participants without formal education (β = 0.661, p <.05) and those aged 29 years or younger (β = 26.927, p <.001), 30–39 years (β = 27.453, p <.001), and 40–49 age group (β = 26.710, p <.001) statistically significantly exhibited an increased food security status compared to their counterparts. Additionally, participants identifying as Akan (β = -0.421, p <.05), Christians (β = -0.828, p <.001), married individuals (β = -0.500, p <.05), those who reported never being ill (β = -2.617, p <.001), those without chronic non-communicable diseases (NCDs) (β = -0.638, p <.001), and those not enrolled in the national health insurance scheme (β = -0.422, p <.01) statistically significantly experienced a decreased food security status compared to their counterparts. Conclusion Considering these findings, policymakers are urged to integrate socio-economic and health characteristics of informal caregivers into food security policies. This inclusive approach is essential for enhancing the food security status of informal caregivers responsible for older adults in slum communities.